Product or service tangible and intangible variables: the creation of the itness application ‘punnett square’ (faps) - Addolorato, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Health and fitness (H&F) industry has always highlighted product’s tangible variables over untouchable ones. Nowadays conspicuous market models are proving that these facets are increasingly required by international societies and contexts and are demonstrated to be incredibly useful. The applicability and usability of fitness resources (products, services or mixed solutions) depends upon a genuinely innovative approach to the definition of those hidden intangible variables. This literature analysis underline that also academic contributions focus more attention on ‘touchable’ variables, but it’s now the time for the ‘B side’. The introduced Fitness Applications ‘Punnett Square’ (FAPS) tool helps to better understand the ever-growing world of fitness industry resources. It is also direct applicable to all those sector professionals who operate in their daily-life facility routine, with the final goal to increase levels of assessment of H&F product and service knowledge, for what already own and for emergent choices or purchasing actions.